Examination of preferences for pork meat and pork meat products among university students - Nagy, Orsolya Bernadett (International Journal of Engineering and Management Sciences, 2020)
The purpose of this study was to examine the preferences for pork meat and pork meat products. The used sample (N=324) for the analysis came from the students of the University of Debrecen Faculty of Economics and Business. The survey was conducted by the form of online questionnaire. The results from data analyzes were based on descriptive statistics, cross-table and correlation analysis, Mann-Whitney and Kruskal-Wallis tests. Based on the results we can concluded that majority of consumers in the sample would be willing to pay more for hungarian and healthier products with less than 50%. Furthermore we can say that have a significant difference between men and women according all factors which used in analysis; have a significant difference between people with secondary and higher education according to perception of manufacturer/brand; have a significant difference between income level groups according to price and healthy eating.